Chemical carbon fractioning in different land uses in the Magdalena Department, Colombia. - Vásquez Polo, José Rafael; Macías Vázquez, Felipe (REVISTA TERRA LATINOAMERICANA, 2017)
Land use change and management can affect the soil’s ability to capture carbon; the magnitude of these changes is unknown in the northern region of the Magdalena Department, Colombia. For this reason, we studied the relationship of the different land uses to contents and forms of carbon in six soil and climate zones in northern Magdalena, Colombia, with altitudes between 5 and 956 m, average temperatures between 24 and 30 °C, and average rainfall between 663 and 2000 mm. In each area, two sites were sampled: tropical crops and forests (Humid and Dry Tropical). Four samples consisting of ten random subsamples per site were taken. In each subsample, we determined total C (Ct), oxidizable C total (Cox), hydrolizable C with 6N HCl (Ch), C linked to humic material (Cp) by extraction with sodium pyrophosphate, rust free C (Cnox) or recalcitrant C calculated as the difference between Ct-Cox, total stored C (Cta) per unit of surface area, which is calculated by taking into account bulk density (Da) and sampling depth. Statistically significant differences were found for the effect of area; the highest percentages of Nt (0.32), Ct (3.90), Cox (3.85), Ch (2.05) and Cp (1.15) and Cta (109 Mg ha‑1) were found in soils of humid forest zone 1 with the highest altitude (956 m), precipitation (2000 mm) and the lowest temperature (24 ºC). Land uses showed significant differences only for NT, CT, Cox, and Ch. The values of the more stable forms of C of forest soils exceeded those of crop soils. Cox and Cnox accounted for 95% and 5% of Ct, respectively, for the different land uses; an average loss of 26% of Ct was observed in cultivated soils as compared with forest soils.